The Effect of Work Autonomy and Workload on Job Satisfaction of Female Workers in the Banking Sector: Mediating the Role of Work Life Balance - Iqbal Ramadhani Fuadiputra; Khusnul Rofida Novianti (Bina Nusantara University, 2020)
The research focused on the role of work-life balance to mediate the effect of work autonomy and workload on female workers’ job satisfaction, particularly in the banking sector. By applying quantitative approach and data collection, the research used questionnaire to 100 female workers in the banking sector in Malang city, East Java, and analyzed using Partial Least Square (PLS) software. The results show that workload has a significant effect on work-life balance. Work autonomy, workload, and work-life balance have a direct and insignificant effect on job satisfaction. Nevertheless, the research highlights the importance of managing work-life balance especially for female workers related to high workload and less autonomy for their job satisfaction in the banking sector especially in Malang.